The My Active and Healthy Aging ICT platform prevents quality of life decline in older adults: a randomised controlled study - Rainero, Innocenzo; Summers, Mathew J; Monter, Michaela; Bazzani, Marco; Giannouli, Eleftheria; Aumayr, Georg; Burin, Dalila; Provero, Paolo; Vercelli, Alessandro E (Age and ageing, 2021)
Prevention of frailty is paramount in older adults. We evaluated the efficacy of a tailored multidomain intervention, monitored with the My Active and Healthy Aging platform, in reducing conversion from a prefrail status to overt frailty and preventing decline in quality of life. We performed a multicentre, multicultural, randomised control study. The effects of multidomain interventions on frailty parameters, quality of life, physical, cognitive, psychosocial function, nutrition and sleep were evaluated in a group of 101 prefrail older subjects and compared with 100 prefrail controls, receiving general health advice. At the 12-month assessment, controls showed a decline in quality of life that was absent in the active group. In addition, active participants showed an increase in mood and nutrition function. No effect on remaining parameter was observed. Our study supports the use of personalised multidomain intervention, monitored with an information and communication technology platform, in preventing quality of life decline in older adults.